Two xanthones and two rotameric (3⟶8) biflavonoids from the Cameroonian medicinal plant Allanblackia floribunda Oliv. (Guttiferae). Issue 52 (26th December 2018) - Mountessou, Bel Youssouf G.; Tchamgoue, Joseph; Paul Dzoyem, Jean; Tchuenguem, Roland T.; Surup, Frank; Choudhary, Muhammad I.; Green, Ivan R.; Kouam, Simeon F.
Graphical abstract: Highlights: Two xanthones and two (3 ⟶ 8) rotameric biflavonoids derivatives were isolated from Allanblackia floribunda . The structures were elucidated on the basis of chemical and spectroscopic data. One of the new biflavonoids, a derivate of morelloflavone revealed remarkable DPPH radical scavenging. Abstract: Two xanthones, 2-(3-hydroxy-3, 3-dimethyldihydroallyl)-dihydro-6-deoxyisojacareubin (1 ) and dihydro-6-deoxyjacareubin (2 ), and two 3 ⟶ 8 rotameric biflavonoids, (2 R, 3 S )-volkensiflavone-7- O - β -acetylglucopyranoside (3 ) and (2 S, 3 S )-morelloflavone-7- O - β -acetylglucopyranoside (4 ), together with fifteen known compounds, were isolated from a dichloromethane/methanol (1:1, v/v ) extract of the bark of the plant Allanblackia floribunda . The structures of the new compounds were elucidated by NMR spectroscopy and mass spectroscopic techniques and those of the known ones were deduced by comparison with data reported in the literature. The isolated biflavonoids were obtained as mixtures of conformers exhibiting duplicate NMR signals in solution at 25 °C and their respective absolute configurations were assigned using circular dichroism spectroscopy. Selected isolated compounds were assessed for their antibacterial and antioxidant properties.